The Peseudo-Static Displacement Calculation of Reinforced and Unreinforced Soil Walls in Frictional Cohesive Soils Using Horizontal Slices Method - Ahmadabadi, Mojtaba; Bahrami, Maryam; Taheri, Zari; Mardani, Samaneh (International Journal of Engineering and Technology, 2018)
Horizontal slices method is a simple and efficient tool for analysis of retaining walls. In this paper, using some of the principles of equilibrium and horizontal slices method, an analytical approach is presented to determine the displacement of concrete walls in the reinforced and unreinforced soils. The formulation of the so-called method is able to calculate wall displacement and critical wedge angle displacement for frictional cohesive soils and draw the distribution of displacement in the wall height. Based on the proposed method, a simple equation is presented to calculate the wedge angle of rupture in the frictional cohesive soils in seismic condition. Comparison of the results with previous methods and numerical methods shows that horizontal slices are able to analyze the concrete wall displacement, while the proposed method has the advantage of analyzing walls via considering soil parameters such as adhesion, seismic coefficients, and the number of reinforcements. In contrast with previous methods that ignored the cohesion concrete wall characteristics, the offered method considers all wall and soil parameters. In addition, design charts are presented for different soils and walls. Considering wall displacement, maximum displacement of wall, displacement of wall apex, and maximum place of wall displacement are obtained, revealing that critical wedge angle displacement is different from rupture wedge angle of pressure imposed on wall.Â